Themes of Classicality in the Malay Architectural Form: Principles from an Aristocratic Realm: (Tema Keklasikan dalam Bentuk Seni Bina Melayu: Prinsip daripada Golongan Bangsawan) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
The term 'classical' in past South East Asian and Malay writings, architectural discourse, cultural studies and urbanism relates to a notion of 'purity' of form, and the traditional vocabulary and forms arising mainly from timber constructions and compositions. This article challenges the current definition by linking it to an aristocratic realm, and argues that selected palaces and mansions of the Malay world embody these universally-understood principles, rules and themes. Such rules of classicality include a keen sense of symmetry, proportionality in form, controlled decorative character and clean lines. This paper explores the frontages and elevational character of these palaces and highlights the underlying themes as reflections of 'the assertive character of aristocratic classicality' which heightened in the context of the evolvement of Malay socio-polities, reflected in certain palatial buildings and aristocratic houses of the late 1800s and early 1900s. The incursion of colonial influences resulted in the evolving of hybrid forms as the Malay socio-cultural landscape underwent changes due to new economic energies and technologies. These palaces reflect local architectural form which underwent changes in technology but essentially held on to the essence of the Malay form. The language of the Malay 'classical' depicts attributes of 'classicality' and a 'highly refined' style, and also reflects certain timeless rules of form. The evolution of these classical forms was occasionally 'interrupted' by colonial elements juxtaposed  upon the original Malay forms. Though at times this diluted the original Malay essence, it did not compromise it. The Malay elements which  survived the onslaught of modernity through colonialism can be considered key rules of Malay architectural and urban character. These are argued as belonging to the same ‘tree’ of Malay architecture which absorbed colonial vocabulary yet has the same root and genealogy.Keywords: Malay classical style, regionalism, hybridity, architectural tectonics, South-East Asian architecture